ATENAS: Um Sistema Gerenciador de Regras de Negócio - Silva, Geraldo Zimbrão da; Almeida, Victor Teixeira de; Souza, Jano Moreira de; Sulaiman, Alberto; Pereira Neto, Francisco Gonçalves (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2001)
Este artigo não possui resumo.